1995
DOI: 10.1093/ajcn/61.3.501
|View full text |Cite
|
Sign up to set email alerts
|

Changes in energy expenditure, anthropometry, and energy intake during the course of pregnancy and lactation in well-nourished Indian women

Abstract: Basal metabolic rate (BMR), thermic effect of a meal (TEM), anthropometry, and dietary intakes were measured in 18 control subjects; 18 pregnant women at 12, 24, and 34 wk gestation; and in 17 of these women at 12 and 24 wk postpartum, to uncover any metabolic economy associated with either pregnancy or lactation. Results indicated that the BMR and TEM were not associated with any energy saving either during pregnancy or lactation. Mean weight gain from 12 wk gestation to term was 11.4 +/- 3.7 kg; mean birth w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
66
0
3

Year Published

1999
1999
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 3 publications
5
66
0
3
Order By: Relevance
“…For this group of poor urban women increasing carbohydrate intake would be the most economical way of increasing energy intake. Piers et al, (1995) also found higher carbohydrate intakes in lactating Indian women at 3 and 6 months pp in comparison to NPNL controls. However, in a longitudinal study of lactating Swedish women Sadurskis et al, (1988) did not find any change in macronutrient composition of the lactating women's diets when compared to their pre-pregnant state.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…For this group of poor urban women increasing carbohydrate intake would be the most economical way of increasing energy intake. Piers et al, (1995) also found higher carbohydrate intakes in lactating Indian women at 3 and 6 months pp in comparison to NPNL controls. However, in a longitudinal study of lactating Swedish women Sadurskis et al, (1988) did not find any change in macronutrient composition of the lactating women's diets when compared to their pre-pregnant state.…”
Section: Discussionmentioning
confidence: 57%
“…For example, lactating women in India, 1 -6 months pp (Madhavapeddi & Rao, 1992;Piers et al, 1995), and in Bangladesh, 2 -8 months pp (Rashid & Ulijaszek 1999), as well as food supplemented women in the Gambia, 3 -9 months pp (Lawrence et al, 1986) were essentially weight stable showing changes in body weight of less than 0.7 kg. In contrast, studies of lactating women in the Philippines, 1-8 months pp (Guillermo-Tuazon et al, 1992), as well as those in Europe (Forsum, et al, 1992;Sadurkis et al, 1988;van Raaij et al, 1991) reported weight losses of 1.3 -1.4 kg in lactating women 1 -7 months pp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The energy intake results from the three sessions (8325 + 1504, 8148 + 1676 and 9419 + 1142 kJaday at 3.5, 10 and 13-months, respectively) are well within the range of the TEE (8554 + 1867, 8555 + 1824 and 9004 + 1818 kJaday) and within the range of energy intakes found from other lactating women living in developing countries. Piers et al (1995) found that energy intake ranged between 9090 and 9600 kJaday over 6 months postpartum for well-nourished lactating Indian women weighing 54 kg, using 5 day weighed dietary records. With a 7 day weighed record, Guillermo-Tuazon et al (1992) obtained a range of energy intake of 8670 ± 8710 kJaday between 1.5 and 7.5 months postpartum among poor rural Philippino lactating women with body weight ranging between 45.4 and 46.9 kg.…”
Section: Energy Balance In Lactating Bangladeshi Women S Vinoy Et Almentioning
confidence: 99%
“…Recently, attention has focussed on lactating women and a number of studies have investigated their energy expenditure and body composition (Goldberg et al, 1991;Adair & Popkin, 1992;Forsum et al, 1992;Guillermo-Tuazon et al, 1992;Piers et al, 1995;Dewey, 1998;Butte et al, 1997Butte et al, ,1999Krebs et al, 1997;Motil et al, 1998;Spurr et al, 1998). However there have been few longitudinal studies beyond 6 months post-partum (cf Lawrence et al, 1986) and most of the subjects were well-nourished mothers (van Raaij et al, 1990;Adair & Popkin, 1992;Motil et al, 1998).…”
Section: Introductionmentioning
confidence: 99%